ANALISIS PERBEDAAN LINGKUNGAN BELAJAR MAHASISWA ANTARA KURIKULUM BERBASIS ISI DENGAN KURIKULUM BERBASIS KOMPETENSI - Susanti -; Dwi Maryanti; Rochany Septiyaningsih (Viva Medika, 2017)
Changes D3 Midwifery Studies Program curriculum must be accompanied by other changes in the management of human resources, facilities and places of learning good practices in order clinic and community level so that graduates can compete well on the order of service of local, regional and international levels. The purpose of this study is to analyze the differences between the students' learning environment based curriculum content with competency-based curriculum. The method used is descriptive comparative coss sectional design using questionnaires Dundee Ready Education Environment Measure (Dreem) by using the Mann-Whitney test analysis. The results of the study there are different expectations on students with curriculum-based content and competency based curriculum in the sub scale dreem there is a difference in subscales of academic achievement and learning atmosphere with p <0.05, whereas in sub-scale learning activities, educators and social problems there differences with p> 0.05. There is a true difference in students with KBI and CBC there are differences in the sub-scale learning activities and educators with a value of p <0.05, whereas in sub-scale academic performance, learning environment and social problems there is no difference with p> 0 05. Conclusion: There are differences between the expectations of the students using the IAC and the CBC on a sub-scale academic achievement and learning atmosphere and the fact there is a difference in subscales of learning and educator. Keywords : curriculum-based content, competency based curriculum, Learning Environment, Student